THE CONNOTATIVE MEANING OF CORONAVIRUS IMPACT EXPRESSIONS IN TEMPO ENGLISH MAGAZINE - Usti Maula; Rahma Ilyas (CALL, 2021)
This research focuses on analyzing coronavirus impact expressions in Tempo English magazine by using theory of connotative meaning from Leech as the grand theory and from Hook as the supporting theory. The focus is on two kinds of connotative meaning, namely, positive and negative connotative meaning. The objectivities of this research are to find out and to explain the use of negative and connotative meaning. The research is qualitative by which helps the researcher to describe the data being studied. In analyzing qualitative data, there are various kinds of methods, including qualitative content analysis. The use of a qualitative content analysis in this research is to know, to describe, and to analyze the use of connotative meaning applied in Tempo English magazine, April 14, 2020 edition. The result of this research is that Tempo English magazine uses many connotative meaning of coronavirus impact expressions. There are 15 expressions as negative connotative meaning and 12 expressions as positive connotative meaning. The findings indicates that the use negative connotative meaning of coronavirus impact expressions in Tempo English magazine are associated with threats in economy sector and associated with inappropriate government policies in an effort to prevent the spread of covid-19 as well as the impact of pandemic in many sectors. Besides, the use positive connotative meaning of coronavirus impact expressions in Tempo English magazine are associated with solutions to avoid spread of Covid-19 as well as solutions to avoid the impact of pandemic, and associated with the government’s responsibility and seriousness in dealing with preventing the spread of coronavirus as well as in dealing with the impact of coronavirus. Keywords: semantics; connotative meaning; coronavirus impact